The Third Gate : Jeremy Logan #3 - Child, Lincoln; Random House Audio Publishing; Recorded Books, LLC. (New York : Random House Audio, 2011)
Porter Stone is leading a team of archaeologists on a search for King Narmer's tomb in the Sudd, a hellish swamp in northern Sudan. The dig, itself, is a nightmare, but the tomb's true horrors have yet to be fully revealed. When several disturbances lead the team to believe they have unleashed a centuries-old curse, Professor Jeremy Logan is called in to investigate.
IN PROCESS RECORD.
Compact disc.
Title from container.
In container (17 cm.)
Keywords: Audiobooks; Suspense fiction